2010
DOI: 10.1111/j.1442-200x.2010.03101.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stability of thyroid hormones and DNA in blood spots kept under varying storage conditions

Abstract: Our data indicate that TT4 and TSH are most stable in blood spots stored at -20°C under continuous power supply. However, they can be stored at RT or at 4°C and -20°C under interrupted power supply for at least 2.5 years. Moreover, the DNA extracted from the blood spots was intact and suitable for genetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…All plasma samples were stored for approximately 1 year at −20°C before analysis of T 4 and TSH. According to the literature (El Ezzi et al 2010; Männistö et al 2007), the concentrations of T 4 and TSH are very stable over time.…”
Section: Methodsmentioning
confidence: 95%
“…All plasma samples were stored for approximately 1 year at −20°C before analysis of T 4 and TSH. According to the literature (El Ezzi et al 2010; Männistö et al 2007), the concentrations of T 4 and TSH are very stable over time.…”
Section: Methodsmentioning
confidence: 95%
“…Although the pertinent literature is quite limited (2)(3)(4)(5)(6)(7)(8), it is undeniably important to establish the best drying and storage conditions of blood samples collected on filter paper for newborn screening. The samples are frequently exposed to different climate conditions during drying and transport to the laboratories, a fact that may influence the test results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the simplicity of this method, which does not require venipuncture and simplifies sample transportation from distant regions to a central laboratory, questions arise about the possible interference of sample drying, storage and transportation under different physical conditions and of the quality of filter paper with the stability of the hormones (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Sera were frozen at −80°C for up to 8.5 months and subjected to 2 freeze‐thaw cycles. Previous studies have shown that dog and cat serum TT4 concentrations remain stable for 35 days at −20°C, and that serum TT4 concentrations in humans remain stable for 6.5 years at −20°C, but no published data are available to our knowledge on the effects of long‐term storage or freeze‐thaw cycles on serum TT4 concentrations in dogs and cats. Given that the MTT4 was repeated at the same time as the CTT4 and ITT4, no effect of storage or freeze‐thaw cycle on the method comparison should have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT4 concentrations Altman plots showed an increasing difference in dogs with TT4 concentrations >5 μg/dL (64.36 nmol/L).This difference would be unlikely to change clinical decisions regarding diagnosis of either iatrogenic oversupplementation or a functional thyroid tumor. The stronger proportional bias evident at values >8 μg/dL (102.98 nmol/L) on Bland-Altman plots would be unlikely to change days at −20 C,9 and that serum TT4 concentrations in humans remain stable for 6.5 years at −20 C,28 but no published data are available to our knowledge on the effects of long-term storage or freeze-thaw cycles on serum TT4 concentrations in dogs and cats. Given that the MTT4 was repeated at the same time as the CTT4 and ITT4, no effect of storage or freeze-thaw cycle on the method comparison should have occurred.…”
mentioning
confidence: 99%